Prophylactic tranexamic acid use in non‐cardiac surgeries at high risk for transfusion. Issue 4 (2nd May 2021) - Houston, Brett L.; Fergusson, Dean A.; Falk, Jamie; Krupka, Emily; Perelman, Iris; Breau, Rodney H.; McIsaac, Daniel I.; Rimmer, Emily; Houston, Donald S.; Garland, Allan; Ariano, Robert E.; Tinmouth, Alan; et al.
Abstract: Background: Tranexamic acid (TXA) reduces transfusion in a wide range of surgical populations, although its real‐world use in non‐cardiac surgeries has not been well described. The objective of this study was to describe prophylactic TXA use in non‐cardiac surgeries at high risk for transfusion. Methods: This is a retrospective cohort study of all adult patients undergoing major non‐cardiac surgery at ≥5% risk of perioperative transfusion at five Canadian hospitals between January 2014 and December 2016. Canadian Classification of Health Interventions procedure codes within the Discharge Abstract Database were linked to transfusion and laboratory databases. TXA use was ascertained electronically from The Ottawa Hospital Data Warehouse and via manual chart review for Winnipeg hospitals. For each surgery, we evaluated the percentage of patients who received TXA as well as the specifics of TXA dosing and administration. Results: TXA use was evaluable in 14 300 patients. Overall, 17% of surgeries received TXA, ranging from 0% to 68% among individual surgeries. TXA use was more common in orthopaedic ( n = 2043/4942; 41%) and spine surgeries (n = 239/1322; 18%) compared to other surgical domains (n = 109/8036; 1%). TXA was commonly administered as a bolus (n = 2097/2391; 88%). The median TXA dose was 1000 mg (IQR 1000–1000 mg). Conclusion: TXA is predominantly used in orthopaedic and spine surgeries, with little uptake in other non‐cardiac surgeries at high risk for red blood cell transfusion. Further studies are needed to evaluate the effectiveness and safety of TXA and to understand the barriers to TXA administration in a broad range of non‐cardiac surgeries.